Criminal policy, trial and immediacy in the time of the COVID-19 - Toyohama Arakaki, Miguel (2020)
The study analyses the importance of managing a criminal policy for the control of organized crime in times of pandemics, due to the expansion of this criminal phenomenon. At the same time, at the hearings and trials, the video conference system is used in simple and complex (criminal organizations) cases. For the purposeexplained, doctrinal, legislative and jurisprudential of these institutions will be examined.